Self Presentation of Idol K-Pop Roleplay Account in Twitter - Prasetyo, Farizqi Feryadhi; Aisyah, Vinisa Nurul (P3M Politeknik Negeri Media Kreatif, 2023)
This study aims to find out how self-presentations are made by users of K-Pop Idol roleplay accounts on Twitter. Roleplay is the activity of someone who assumes himself as another person or in a certain role. This research was conducted concerning the dramaturgical theory of Erving Goffman. This research is a type of descriptive qualitative research. In this study, data were obtained through observation and interviews which were then analyzed using interactive data analysis techniques. The results obtained in this study indicate that the resource person's roleplay account is the front stage which contains settings, appearance, and manner. Meanwhile, the back stage of the informant is the original life of the resource person which then becomes a place of preparation to form self-concept or impressions in the world of roleplay. Self-presentation can be seen from the appearance of the speakers on the front stage. While the preparation in the back stage includes the concept of identity, reference and motivation. Apart from that, in the back stage, the informant tends to hide the fact that he is a roleplayer